Political, Social Exchange in The Selection of Concurrent Regional Heads in Indonesia - Chupradit, Supat; Joompathong, Natthanit; Chupradit, Priyanut Wutti (International Journal of Psychosocial Rehabilitation, 2020)
This research has the objective for studying the relationship between the behavior of using the internet with the social skill of the university student. By this will use the quantitative studying method which will gather the information from the sample such as; 500 of 1st year students who have lived in the dormitory of Chiang Mai University. Using tools will be the basic questionnaire of the sample, the evaluating form of using the internet and the evaluating form of the social skill, Standard Deviation and the analysis with inferential statistic. By this will use Pearson’ Product Moment Correlation Coefficient, the studied result is found that most of the sample will have addicted to the internet usage in a few level. And most of them will have the social skill in the moderate level. For the sample who haven’t addicted to the internet usage, most of them will have the high social skill level. For the sample who have addicted to the internet usage in a few level, the moderate level and the severe level, most of them will have the moderate social skill. In order that, from testing of Pearson’ Product Moment Correlation Coefficient between the behavior of using the internet with the social skill, this is found that; (1) The behavior of using the internet with the social skill will have the negative relationship in a few level. The correlation coefficient value will be equal to -.320. By this will have the statistical significance at the level of 0.01. (2) The behavior of using the internet with the social skill in the capacity in the communication and the interaction will have the negative relationship in a few level. This will have the correlation coefficient value that is equal to -.234. By this will have the statistical significance at the level of 0.01. and (3) The behavior of using the internet with the social skill in the capacity in working as the group will have the negative relationship in a few level. This will have the correlation coefficient value that is equal to -.289. By this will have the statistical significance at the level of 0.01.